Nilai, Struktur, dan Perlawanan dalam Relasi Kerja Agensi Kreatif - Grace Tobing (Calathu: Jurnal Ilmu Komunikasi, 2025)
This study explores labor relations within the creative industry, focusing on a creative agency in Bandung, Indonesia. Using Robert E. Stake’s multiple case study approach and qualitative methods through semi-structured interviews, the study examines how organizational values and work culture are shaped, socialized, and negotiated in daily practices. Drawing on Antonio Gramsci’s theory of hegemony, the analysis demonstrates how symbolic consensus and managerial language operate as persuasive rather than coercive forms of power. This study examines how organizational values are disseminated and internalized, how the structure of work shapes worker consciousness and behavior, and how workers respond to symbolic domination embedded in daily work practices. Employing a qualitative approach and multiple case study method, the research involves semi-structured interviews with creative workers. The findings reveal that workplace hegemony operates not only through coercion but also through persuasion, by normalizing ideals such as passion, loyalty, and flexibility. However, various forms of resistance emerge through micro-practices, meaning negotiation, and emotional distancing from corporate values. This research contributes to critical perspectives on hidden power relations in the seemingly free and fun culture of creative labor.